Body fat levels and its negative correlation to apnea duration - Kukuh Pambuka Putra; Rambu Lawu Nedi Kristanti Retno Triandhini; Aditya Wicaksana; Sanfia Tesabela Messakh (Jurnal Keolahragaan, 2022)
Apnea ability is the main determining factor of freediving performance. Apnea relates to physiological factors that might be experienced by a free diver hence its ability is highly likely to correlate with various factors of human physiology. One of the suspected factors that affect apnea duration is body fat level. The fact that fat is distributed in almost all parts of the body, including respiratory organs and tracts, arises the suspicion of a possible correlation between fat accumulation and apnea ability. This research studies the correlation between body fat level and apnea duration. 30 males, aged 18-22 were the research participant. Body fat levels were measured using Bioelectrical Impedance Analyzer, while apnea duration was measured by the length of which the participants hold their breath while sitting silently in the pool. The obtained data were then analyzed using a series of tests: normality, correlation, and linear regression tests. Pearson Correlation test shows negative result (p0,05) with the value of correlation coefficient -0.611 which means negative correlation with medium strength. The result of the linear regression test also shows a similar value of 0.611. Meanwhile, the value of the determinant coefficient (R square) is 0.374 (37.4%). Based on the value obtained, it can be inferred that body fat levels have 37.4% influence on the duration of apnea, while the other 62.2% are influenced by a variety of other factors